TYPES, CAUSES AND CONSEQUENCES OF UNEMPLOYMENT (American Journal of Business Management, Economics and Banking, 2024)
The article is devoted to a comprehensive analysis of the problem of unemployment, its causes, types, consequences and methods of public policy in this area. Macroeconomic factors are considered, such as the decline in production and structural changes in the economy, as well as the individual characteristics of workers that affect their competitiveness in the labor market. Particular attention is paid to the economic, social and personal consequences of unemployment. Key areas of state employment policy are analyzed, including measures to stimulate the creation of new jobs, social support for the unemployed and activities employment services. The article may be useful to economists, labor market specialists, as well as anyone interested in employment issues